Post-term birth as a response to environmental stress: The case of September 11, 2001 - Margerison-Zilko, Claire E. (Evol Med Public Health, 2015)
Background and objectives: Despite growing interest in the role of maternal psychosocial stress as a determinant of preterm birth, no existing work has examined the relation between maternal stress and post-term birth (≥42 weeks). We hypothesize that prolonging gestation past term may represent an adaptive strategy to a suboptimal environment. Methodology: We examined the relationship between exposure to the September 2001 terrorist attacks and odds of post-term birth in California. We calculated the expected odds of post-term birth among conception cohorts of singleton gestations in California between October 1996 and November 2005. We used time series analysis to test for higher than expected odds of post-term birth among the 10 cohorts exposed to the attacks of September 2001 (those conceived from December 2000 to September 2001). Results: The observed odds of post-term delivery among gestations at 33–36 weeks in September 2001 were higher than statistically expected for all race/ethnic and sex groups. Conclusions and implications: Our finding that odds of post-term birth were higher than expected among pregnancies exposed to the September 2001 terrorist attacks in late gestation provides initial support for the hypothesis that exposure to a psychosocial stress during pregnancy may result in prolonged gestation.